Estudo comparativo entre modelos de propaga????o para ondas milim??tricas - Marengo, Gustavo Kreuzer (2022)
This work presents a comparative analysis of the estimated losses, which are calculated using the following propagation models for millimeter waves: Free Space; NYUSIM; mmMAGIC; METIS; 5GCM; 3GPP.TR.38.901; ABG; CI. Specifically, campaign measurements of the fifth generation of mobile communications (5G) networks in the 28 GHz band, from the specialized literature, have been used for the mentioned calculations. The main goal of this work is to verify the accurace of the loss estimations for indoor and outdoor scenarios, under line of sight (LOS) and non-line of sight (NLOS) conditions. The quantitative comparison metric was MAPE (Mean Absolute Percentage Error). In addition, the field measurement uncertainty error was evaluated, with the purpose of comparing it with the loss estimation error obtinaed using MAPE for each model in the studied environments.